2019
DOI: 10.1371/journal.pone.0210494
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of feeding by four sympatric Neotropical primates (Ateles belzebuth, Lagothrix lagotricha poeppigii, Plecturocebus (Callicebus) discolor, and Pithecia aequatorialis) in Amazonian Ecuador: Relationships to photic and ecological factors

Abstract: We examined photic and ecological factors related to initiation of feeding by four sympatric primates in the rain forest of Amazonian Ecuador. With rare exceptions, morning activities of all taxa began only after the onset of nautical twilight, which occurred 47–48 min before sunrise. The larger spider and woolly monkeys, Ateles belzebuth and Lagothrix lagotricha poeppigii, left their sleeping trees before sunrise about half the time, while the smaller sakis and titi monkeys, Pithecia aequatorialis and Plectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…The climate is hot and humid, with mean monthly temperatures of 24–27°C throughout the year (Van Belle, Fernandez‐Duque, & Di Fiore, ). Mean annual precipitation is 2,924 ± SD 267 mm (2009 to 2014) with the wettest period occurring from March through June (Snodderly et al, ). Additionally, between 2000 and 2001, one of us (MH) conducted a 16‐month field study on wild mustached tamarins ( S. mystax mystax ) at the Estación Biológica Quebrada Blanco (EBQB, 73°09’ W, 4°21’ S, about 120 m above sea level, encompassing ca.…”
Section: Methodsmentioning
confidence: 99%
“…The climate is hot and humid, with mean monthly temperatures of 24–27°C throughout the year (Van Belle, Fernandez‐Duque, & Di Fiore, ). Mean annual precipitation is 2,924 ± SD 267 mm (2009 to 2014) with the wettest period occurring from March through June (Snodderly et al, ). Additionally, between 2000 and 2001, one of us (MH) conducted a 16‐month field study on wild mustached tamarins ( S. mystax mystax ) at the Estación Biológica Quebrada Blanco (EBQB, 73°09’ W, 4°21’ S, about 120 m above sea level, encompassing ca.…”
Section: Methodsmentioning
confidence: 99%
“…Although there is not a pronounced dry season, rainfall can vary dramatically between months. March through July are consistently the wettest months of the year with ≥250 mm of rain falling each month, while August and September tend to be drier, with rainfall increasing again in October, peaking in November, then drying off again for December and January (Snodderly et al, 2019). Still, there is a considerable interannual variation that muddies this pattern (Snodderly et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…March through July are consistently the wettest months of the year with ≥250 mm of rain falling each month, while August and September tend to be drier, with rainfall increasing again in October, peaking in November, then drying off again for December and January (Snodderly et al, 2019). Still, there is a considerable interannual variation that muddies this pattern (Snodderly et al, 2019). Because of its location near the equator, photoperiod is consistent throughout the year, although the timing of sunrise may vary as much as 30 min during a biannual cycle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies of sympatric and non-sympatric primates have indicated that diet and space are factors affecting competition and conflict. Several studies on primate populations have shown that primates adopt various strategies for coexistence—for example, Snodderly et al ( 2019 ) reported that four sympatric species, Ateles belzebuth, Lagothrix lagotricha poeppigii, Plecturocebus discolor, and Pithecia aequatorialis , adopted temporal niche partitioning by feeding at different diurnal periods. Competitive food exclusivity in Diana monkeys ( Cercopithecus diana ) maintained resource partitioning by allowing access to fruit-rich diets through competitive exclusion of sympatric congeners (Kane and McGraw 2017 ).…”
Section: Introductionmentioning
confidence: 99%